EKSTRAKSI TANIN DARI KULIT KAYU AKASIA DENGAN MENGGUNAKAN MICROWAVE: PENGARUH DAYA MICROWAVE, WAKTU EKSTRAKSI DAN JENIS PELARUT - Iriany; Florentina Pandiangan; Christina Eka P (Talenta Publisher (Universitas Sumatera Utara), 2017)
Tannin is one of complex polyphenol compound which soluble in polar solvent. Tannin could be extracted from acacia bark. This study aims to examine microwave-assisted extraction of tannins under influence of microwave power, extraction time, and solvent and its application to adsorb Cd and Cu. Tannin was extracted from acacia bark with feed-to-solvent ratio (1:20 g/ml). Power of microwave was adjusted 100 W, 180 W, 300 W, 450 W, and 600 W for 1 minute, 3 minutes and 5 minutes respectively using aquadest and ethanol as the solvent. The extracts were analyzed using UV-Vis spectrophotometer. Furthermore, the extract with the highest yield of tannins are used as the adsorbent. The concentration of Cd and cu were analyzed using Atomic Absorption Spectrophotometer. The result showed the highest yield of tannin 26.606 mg/g at 100 W and 3 minutes extraction time using ethanol as the solvent. The result showed that the adsorption capacity of adsorbent from tannin was 3.81 mg/g and 2.26 mg/g for Cd and Cu respectively.